Enantioselective iridium-catalyzed allylic substitutions with hydroxamic acid derivatives as N-nucleophiles - Gärtner, Martin; Jäkel, Mascha; Achatz, Manuel; Sonnenschein-Battefeld, Christoph; Tverskoy, Olena; Helmchen, Günter (Organic letters, 2011)
Enantioselective Ir-catalyzed allylic aminations with hydroxamic acid derivatives are described. Catalysts were prepared in situ from [Ir(cod)Cl]2 or [Ir(dbcot)Cl]2, a phosphoramidite and base. In addition, pure (π-allyl)Ir complexes containing cod or dbcot as auxiliary ligands were used. Very high degrees of regio- and enantioselectivity were achieved. The reaction products were transformed into piperidine derivatives suited as precursors for aza-sugars.
Gesehen am 03.08.2023